(3GdJMGdaGJ GdESJQGJjLjI aj efXeGJ GdCYeGd (B:s (3eaGgje (B-(3eOGNd (B-(3JWHjbGJ (B/s - (3GdYfRj, SYO Ydjs; (3QGVj, LhGO eMSf s ((3YeGf(B: s (3OGQ GdjGRhQj(B, s, 2011)
(3eaghe GdJMGdaGJ GdGSJQGJjLjI h OhGaYgG Ydi eSJhi efXeGJ GdGYeGd (B: (3CfhGY GdJMGdaGJ GdGSJQGJjLjI h JUfjaGJgG , efXhQGJ GdJMGda GdGSJQGJjLj aj GWGQ MGcejI GdTQcI , OjfGejcjGJ GdJYGhf Hjf efXeGJ GdGYeGd h GSJQGJjLjGJgG ,adSaI GdJfGaSjI aj GOGQI GdGYeGd h OjfGejcjGJgG , OQGSGJ eQLYjI egeI aj GdJMGdaGJ GdGSJQGJjLjI , OQGSI MGdI aj JTNjU JTcjd GdJMGdaGJ GdGSJQGJjLjI aj efXeGJ GdGYeGd , GNJHGQ YdGbGJ GdGQJHGW h GdJCKjQ Hjjf eJZjQGJ JTcjd GdJMGdaGJ GdGSJQGJjLjI (B.s
(3eQGLY (B: (3dcd aUd eQLY ; edGMb U(B.401s
Keywords: (3EOGQI GdCYeGds; (3efXeGJ GdCYeGds